The Influence of Competency Development and Organizational Communication through Job Satisfaction as a Mediating Variable at the General Elections Commission (KPU) in Banten Province - Tamami, Maman; Maliki, Budi Ilham; Komarudin, Mamay (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The Banten Province General Elections Commission (KPU) faces challenges in employee performance, particularly in terms of task completion accuracy, conflict management, and regulatory compliance. Low training participation and weak organizational communication contribute to decreased work effectiveness. This study aims to analyse the effect of competency development and organizational communication on employee performance, with job satisfaction as a mediating variable. A quantitative approach with an explanatory design was used. A sample of 150 Banten Provincial General Elections Commission (KPU) employees was selected using the Hair et al. technique. Data were collected through questionnaires and analysed using Partial Least Squares-based Structural Equation Modelling (PLS-SEM) to test direct and indirect relationships between variables. The results show that competency development and organizational communication have a positive and significant effect on job satisfaction. Job satisfaction also significantly influences employee performance. Furthermore, job satisfaction significantly mediates the effect of competency development and organizational communication on performance. These findings support Human Capital theory, which emphasizes the importance of investing in competencies and the work environment. Improved competencies and effective internal communication can boost employee job satisfaction and performance. The practical implications of this research underscore the need for the General Elections Commission (KPU) to design a human resource development policy based on continuous training and to establish a transparent organizational communication system. This model has the potential to be adapted by other public organizations to improve the effectiveness of public services